LONG-TERM OUTCOME IN PATIENTS WITH MYOCARDIAL INFARCTION AFTER REPERFUSION THERAPY - Yu.O. Sychenko (Bogomolets National Medical University, 2016)
We performed a retrospective analysis of case histories of patients with myocardial infarction with ST- segment elevation (STEMI), which have been consistently hospitalized in the Alexander clinical hospital of Kyiv in 2011-2013 and received thrombolytic therapy or PCI in the first 12 hours after development of chest pain. After discharge from the hospital patients were followed up for 3 years, making telephone survey. At the end of the period of observation we analyzed data of 180 (53.6%) patients. End points were nonfatal myocardial infarction, cardiovascular death (CVD) and the combined endpoints, which included nonfatal MI and CVD, nonfatal MI, CVD and hospitalization for cardiovascular diseases (unstable angina, heart failure). Depending on the type of reperfusion therapy, patients were divided into 2 groups: the 1st group included 115 patients who received thrombolytic therapy, 2 nd - 65 patients who completed PCI. We analyzed factors that were associated with increased incidence of CVD and increase of combined end-points during 3 years of follow- up.The average age of patients after TLT and PCI was 65,1 ± 0,9 and 64,6 ± 1,5 (p> 0.05) years, respectively. Patients in both groups did not differ by gender, localization of myocardial infarction, frequency of hypertension, diabetes, history of myocardial infarction, signs of acute heart failure of II-III Killip class, TIMI-risk, ischemia time and EF (all p>0,05). We did not find any differences between endpoints in groups of TLT and PCI, the proportion of patients with recurrent MI was 16.5 and 7.7%, respectively (p>0.05), CVD - 18.3 and 9.2%, respectively (p>0.05). After PCI at long-term observation achieving of all combined endpoints were lower compared with patients after TLT (all p<0,05).Mortality was associated with higher (>5 points) Timi risk score (p<0.05). There were no significant negative associative connection for 3-year mortality rate of resolution of ST e"50% in 90 minutes after TLT (OR [95% CI] = 0,74 [0,47-1,18]; p = 0, 06) and resolution of ST e"70% in 30 minutes after PCI (OR [95% CI] = 0,61 [0,36-1,02]; p = 0,08). There was no association with type of PCI and epicardial bloodstream after it (p>0.05). Primary PCI in a long-term follow-up show better results comparing to TLT in 93% performed with streptokinase. Established that failure to reach resolution of STe"50% at 90 minutes after TLT and STe"70% at 30 minutes after PCI is associated with increased incidence of CVD and the increased incidence of the combined endpoint (CVD, re-infarction, rehospitalization) over the next three years of observation 2 times higher.Patients with high Timi risk score have a higher mortality in the long term, regardless of the type of reperfusion therapy. The presence of high Timi risk score for > 5 is an independent predictor of 3 year mortality.